Integration of AI Technology in E-Commerce as an Effort to Realize Consumer Protection Law - Nadia Ramadhani Octora; Rizka Syafriana (ISNU Sumatera Utara, 2025)
An agreement is a legal act carried out by two or more parties, where one party is obliged to do something, while the other party is entitled to the fulfillment of obligations. Along with the development of the times, there has been a new breakthrough in making transactions, namely through electronic media facilities or what can be called e-commerce. Therefore, this study focuses on how the Validity of Sale and Purchase Agreements Through E-Commerce Platforms is reviewed based on Indonesia's Positive Law and How Legal Protection for Consumers for Sale and Purchase Agreements Through Electronic Transactions Based on the Consumer Protection Law. This study uses a normative juridical research method, with analytical descriptive research specifications using data sourced from several previous studies. This research concludes that Sale and Purchase Agreements through E-Commerce Platforms can be considered valid as long as they remain subject to the Civil Code and the ITE Law. In addition, legal protection for consumers can be realized in two forms of regulation, one of which is legal protection through legislation, in this case Law No. 8 of 2010 concerning consumer protection. Protection for merchants in buying and selling transactions through e-commerce platforms that merchants have their rights as legal protection in accordance with Article 6 of the Consumer Protection Law.